Klasifikasi Emas Indonesia Sebagai Hedge dan Sage Haven Asset dalam Pasar Sahan Domestik, Pasar Saham Luar Negeri, dan Pasar Dolar AS Tahun 2008-2015 - Marini Syafitri; Aisyah Fitri Yuniasih (Jurnal Aplikasi Statistika & Komputasi Statistik, 2016)
Gold is supposed to be one of the promising investment instruments because it has good characteristics as a means for investment diversification (O'Byrne and O'Brien (2013)). However, during post-global crisis, especially in 2009, Indonesian gold investment was lower than before. This study aims to identify the classification of Indonesian gold in terms of its strength and its role in the domestic and foreign stock market as well as the US Dollar market, in both normal condition and bullish and bearish conditions in 2008-2015. This study uses the ARDL model in its analysis of hedge and safe haven of Indonesian gold. It indicates that the Indonesian gold, in general, act as a weak hedge asset in the international stock market, a strong hedge asset in the US Dollar market, a strong safe haven asset in the domestic and international stock market and a weak safe haven in the US Dollar market.